Rehabilitación urbano arquitectónica del Instituto Materno Infantil de Bogotá (2021)
The Instituto Materno Infantil is a historic architectural monument that for almost a century has been present in the lives of citizens, its importance for medicine, urban planning and architecture is incalculable. However, due to a series of problems this place with the passage of time has faded its legacy and today its relevance is limited, despite having been the epicenter of neonatal medicine in the capital city. The problems of this heritage object are reflected at the architectural, urban and functional levels